Effectiveness of flaxseed consumption and fasting mimicking diet on anthropometric measures, biochemical parameters, and hepatic features in patients with Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD): a randomized controlled clinical trial - Navideh Khodadadi; Amir Sadeghi; Hossein Poustchi; Behnood Abbasi; Maryam Nilghaz; Ebru Melekoglu; Zahra Yari; Azita Hekmatdoost (Nutrition & Diabetes)
Abstract Background and aim Although benefits of flaxseed and fasting mimicking diet (FMD), each alone, have been shown in the management of metabolic dysfunction-associated steatotic liver disease (MASLD), the benefit of combining the two is not clear. This study aimed to investigate the effect of the combination of FMD and flaxseed supplementation on surrogate measures of MASLD. Methods The present study was conducted as a randomized, parallel, open-label controlled clinical trial on a hundred patients with MASLD for 12 weeks. Eligible participants were assigned to four groups including control group (lifestyle modification recommendations); flaxseed group (30 g/day of flaxseed powder consumption); FMD group (16 h of fasting per day), and combination of FMD with flaxseed. Changes in anthropometric parameters, serum levels of lipids, glycemic measures, High-sensitivity C-reactive protein (hs-CRP), and liver enzymes, and hepatic steatosis and fibrosis by transient elastography were assessed. Results Serum triglycerides, total cholesterol, fasting blood glucose and insulin, hs-CRP and liver enzymes decreased in all intervention groups. Hepatic steatosis score decreased in the intervention groups, but not significantly in comparison to the control group. Hepatic fibrosis score decreased significantly in the intervention groups compared to control. Conclusion Our data indicate that the combination of FMD with flaxseed consumption is not superior to either of the interventions alone in the management of MASLD.